Thiazolidine Derivatives Attenuate Carrageenan-Induced Inflammatory Pain in Mice - Malik Z; Abbas M; Al Kury LT; Shah FA; Alam M; Khan AU; Nadeem H; Alghamdi S; Sahibzada MUK; Li S (Dove Medical Press, 2021)
Zulkifal Malik,1,2 Muzaffar Abbas,2 Lina Tariq Al Kury,3 Fawad Ali Shah,1 Mahboob Alam,2 Arif-ullah Khan,1 Humaira Nadeem,1 Saad Alghamdi,4 Muhammad Umar Khayam Sahibzada,5 Shupeng Li6 1Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, Pakistan; 2Faculty of Pharmacy, Capital University of Science and Technology, Islamabad, Pakistan; 3College of Natural and Health Sciences, Zayed University, Abu Dhabi, United Arab Emirates; 4Laboratory Medicine Department, Faculty of Applied Medical Sciences, Umm Al-Qura University, Mecca, Saudi Arabia; 5Department of Pharmacy, Sarhad University of Science and Information Technology, Peshawar, KPK, Pakistan; 6State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, People’s Republic of ChinaCorrespondence: Muzaffar AbbasFaculty of Pharmacy, Capital University of Science and Technology, Islamabad Expressway, Kahuta Road, Zone-V, Islamabad, PakistanTel +92-51-111555666Fax +92-51-4486705Email Muzaffar.abbas@cust.edu.pkShupeng LiState Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Shenzhen, 518055, People’s Republic of ChinaEmail lisp@pku.edu.cnBackground: Peripheral inflammation leads to the development of persistent thermal hyperalgesia and mechanical allodynia associated with increased expression of interleukin-1β (IL-1β) in the spinal cord. The aim of the present study was to investigate the effects of thiazolidine derivatives, 1b ([2-(2-hydroxyphenyl)-1,3-thiazolidin-4-yl](morpholin-4-yl)methanone) and 1d (2-hydroxy-4-{[2-(2-hydroxyphenyl)-1,3-thiazolidine-4-carbonyl]amino}benzoic acid), on thermal hyperalgesia, mechanical allodynia and on IL-1β expression during carrageenan-induced inflammation in the spinal cord in mice. Inflammatory pain was induced by injecting 1% carrageenan into the right hind paw of the mice.Methods: The animals were administered thiazolidine derivatives, 1b and 1d (1 mg/kg, 3 mg/kg, or 10 mg/kg), intraperitoneally 30 minutes before carrageenan administration. The animals’ behavior was evaluated by measuring thermal hyperalgesia, mechanical allodynia, and motor coordination. The IL-1β expression was measured by enzyme-linked immunosorbent assay. Acute and sub-acute toxicity studies were conducted to evaluate the toxicity profile of compounds.Results: Treatment with the thiazolidine derivative, 1b and 1d, attenuated carrageenan-induced thermal hyperalgesia and mechanical allodynia at doses of 1 mg/kg, 3 mg/kg, and 10 mg/kg. No motor coordination deficits were observed in animals. The compounds also reduced IL-1β expression in the spinal cord of mice. Acute and sub-acute toxicity studies revealed that both compounds were safe.Conclusion: The compounds exhibit promising activity against inflammatory pain due to their ability to produce anti-hyperalgesic and anti-allodynic effects and to inhibit IL-1β expression in the spinal cord.Keywords: inflammatory pain, IL-1β, thiazolidine derivatives, mechanical allodynia, thermal hyperalgesia